Consistency Analysis of Spectral Regularization Algorithms - Yukui Zhu; Hongwei Sun (Abstract and Applied Analysis)
We investigate the consistency of spectral regularization algorithms. We generalize the usual definition of regularization function to enrich the content of spectral regularization algorithms. Under a more general prior condition, using refined error decompositions and techniques of operator norm estimation, satisfactory error bounds and learning rates are proved.